A review of the circuit-level and cellular mechanisms contributing to locomotor acceleration in the marine mollusk Clione limacina - Pirtle, Thomas J. (Frontiers in Neuroscience, 2022)
The pteropod mollusk, Clione limacina, is a useful model system for understanding the neural basis of behavior. Of particular interest are the unique swimming behavior and neural circuitry that underlies this swimming behavior. The swimming system of Clione has been studied by two primary groups—one in Russia and one in the United States of America—for more than four decades. The neural circuitry, the cellular properties, and ion channels that create and change the swimming locomotor rhythm of Clione—particularly mechanisms that contribute to swimming acceleration—are presented in this review.